2019
DOI: 10.29313/gmhc.v7i1.2908
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mixed-Fruit Juice on Uterine Contractions and Cervical Dilatation During the First Stage of Delivery

Abstract: Energy imbalance in delivery can inhibit the action of glycolytic enzymes and interfere with chemical reactions in muscle cells. These nuisances may interfere with uterine contractions that obstruct cervical dilatation. Therefore, mothers require a nutritional alternative which is practical, generates energy quickly and supplies glucose needed for uterine contractions. These can be fulfilled with a mixed-fruit juice beverage. Mixed-fruit juice consists of fruits, Tunisian dates, honey, and red beans. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The results of research by Martasari et al, (2019), combined dates into a mix-juice with a mixture of fruit, Tunisian dates, honey and red beans, which was given to 30 mothers giving birth during the first stage of the latent phase. The results showed that giving mixed date juice during the first stage of labor had an effect on the progress of uterine contractions and cervical opening.…”
Section: Discussionmentioning
confidence: 99%
“…The results of research by Martasari et al, (2019), combined dates into a mix-juice with a mixture of fruit, Tunisian dates, honey and red beans, which was given to 30 mothers giving birth during the first stage of the latent phase. The results showed that giving mixed date juice during the first stage of labor had an effect on the progress of uterine contractions and cervical opening.…”
Section: Discussionmentioning
confidence: 99%
“…18 Inadequate uterine activity is considered to be the cause of the increasing number of abnormal labor. 7,21 Thus, other interventions should be highly considered before cesarean delivery is resorted to for the management of non-progressive labor. 6,20 Interestingly, previous research has shown that dates are high in prostaglandins.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Energy imbalance during labor can inhibit the action of glycolytic enzymes and interfere with chemical reactions in muscle cells, resulting in the inhibition of muscle contraction and cervical dilatation. 7 Weak uterine contractions or inadequate contractions are caused by non-smooth labor. 8,9 One of the non-pharmacological therapies to trigger the performance of the oxytocin hormone and accelerate the first stage of labor is to consume fresh dates (Phoenix Dactylifera), 7 which have important nutrients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations